Volumetric mass transfer coefficient in the fermenter agitated by Rushton turbines of various diameters in coalescent batch. (March 2019) - Petříček, Radim; Moucha, Tomáš; Kracík, Tomáš; Rejl, František Jonáš; Valenz, Lukáš; Haidl, Jan
Highlights: Experimental k L a data for pilot-plant and laboratory fermenters are presented. Experimental k L a data for Rushton turbines in coalescent batch are presented. Rushton turbines of various diameters are used. KL a correlation shapes are suggested for fermenters design. Abstract: The volumetric mass transfer coefficient kL a becomes the crucial parameter for mechanically agitated fermenters design. Prediction of kL a is commonly based on literature correlations. In the case of coalescent liquids, literature-based correlations don't provide results with acceptable scatter. Our aim is to establish viable kL a correlations for coalescent liquids that would be based on great experimental data set obtained using Dynamic Pressure Method, the physical correctness of which was verified earlier. In our previous work, the kL a dependencies on process conditions in a viscous liquid were described in terms of an appropriate correlation. Now, we aim at the description of dependency between impeller diameters and transport characteristics in coalescent batch. The measurements were performed in multiple-impeller vessels of both laboratory and pilot-plant scale, and for various experimental conditions (impeller frequencies, gas flow-rates, impeller diameters). The studied impellers were Rushton turbines with diverse diameters. On the base of experimental results, the accurate correlation for kL a prediction in coalescent batch for industrial devices was suggested. Both the experimental technique and the correlation shape could be used for an industrial design of fermenters with coalescent batches.